Students’ Perception Toward Animation On Teaching Speaking Skill At University Technology Mara (UiTM) - Azlan Bin Shaiful Baharum; Amanee Abdul Hai (AL-HAJJAJ Enterprise, 2024)
This study attempts to analyze student’s perception toward using animation in developing speaking skill in Arabic language subject. This study involves 132 students from University Technology MARA (UiTM), Rembau, Negeri Sembilan. A set of quantitative questionnaires is built to gain data for the research. These data then be analysed descriptively to find out the distribution of frequency, percentage and mean. The result of this study indicates that the students have high perception and respond positively towards the using of animation as teaching tool in learning Arabic language with the mean (4.1). The study supports that the animation is an additional practical way to teach Arabic language and contribute to attracting students’ interest to master it.